Influence of Geometry and Boundary Conditions in Area of the Cohesion between Materials on the Reflection of an Ultrasonic Beam. Part 2. Features of Experimental Simulation - A. R. Baev; N. V. Levkovitch; M. V. Asadchaya; A. L. Mayorov; G. I. Razmyslovich; A. Y. Burnos (Приборы и методы измерений, 2021)
Improving the efficiency of diagnostics of objects with layered structure as applied to detection of poorly detectable material bonding defects is an important production task. The aim of the work was to experimentally simulate ultrasonic scattering by samples of proposed defect simulator designs with discretely and smoothly varying boundary conditions correlating with the phase response of longitudinal waves during their interaction with the defect boundary of contacting materials.A brief analysis of some methods and means for experimental simulation of the volume and surface wave scattering at the interfaces of contacting materials as applied to improvement of method of detection of poorly detectable adhesion defects of materials proposed earlier was carried out. For this purpose an immersion installation working in the shadow mode and allowing for simulation the spatial fields of scattered longitudinal waves at inhomogeneous or defective adhesion boundaries was developed and constructed. It is assumed that the waves interacting with such a boundary acquire a discrete or smoothly varying phase shift which significantly affects the formation of the scattering field in its peripheral zone. The greater this shift, the stronger these changes are, which can significantly increase the sensitivity of detection of poorly detected defects.In order to increase the efficiency of such inspection and to develop its methodology a new principle of simulation of such defects has been proposed.Experimental study of longitudinal waves scattering using the developed installation and defect simulators, simulating discretely and smoothly changing boundary conditions which are consistent with a change in the phase shift of the scattered waves is carried out. The amplitude dependences of the scattering field vs. the receiving angle received mainly in the range from - 20º to + 20º and the displacement of the simulated defect relative to the axis of the probing acoustic beam were obtained.As it has been established, there is a quality conformity between the calculated and experimental data. The present study is of interest for solving a number of tasks of increasing efficiency of ultrasonic testing of modern objects with layered structure and will contribute to practical application.